Diagnosis of Acute Pancreatitis as a Compilation of Weil's Disease - Rabbinu Rangga Pribadi; Christy Efiyanti; Rio Zakaria; Ari Fahrial Syam; Leonard Nainggolan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTWeil’s disease is a severe form of leptospirosis and caused by pathogenic strain of Leptospira. Weil’s disease affects many organs including pancreas. Acute pancreatitis in leptospirosis is quite rare. Diagnosis of acute pancreatitis in Weil’s disease is based on clinical features, biochemical, and radiologic examination. Sometimes histopathological examination is urged to confirm diagnosis. Management of acute pancreatitis in severe leptospirosis comprise of antibiotic for leptospirosis and supportive treatment for the acute pancreatitis. Early and appropriate treatment is mandated as it was studied to significantly decrease mortality riskWe reported a case of 42 year old man suffering Weil’s disease with multi organ complications. Patient complained diffuse abdominal pain. Although the abdominal ultrasonography did not show any abnormalities of the pancreas, the amylase and lipase showed striking results. He recovered uneventfully. This case report demonstrated acute pancreatitis as one of severe leptospirosis complications. Keywords: acute pancreatitis, Weil’s disease, severe leptospirosis